Gender Stereotype Towards Children in a Social Resilience Perspective - Zulfiyan, Ahmad (Martabat: Jurnal Perempuan dan Anak, 2020)
Social-relational lives among both female and male children often experience various problems of gender injustice, which are manifested in the form of gender stereotype. The aim of this paper is to analyze some aspects of gender stereotype and their implications for social resilience towards children especially in context of relations between both female and male children and also for their environment. The data collection relies on two aspects, first is literature study and second is interview which is conducted for one expert whose background is as an academician and also an activist for children rights. This study asserts that gender stereotype has been done since childhood, even before the child has been born. The stereotype is perpetuated through various socializations: through families, schools, and the general public environment. Gender stereotype has an impact on children’s social resilience, particularly on how children react it among society. The difference of perceptions in children with society expectations makes them feel confused, insecure, and uncomfortable among society.